Intratubular penetration depth of ultrasound activated bioceramic sealant cements at the dentin-radicular cement interface = Profundidad de penetración intratubular de cementos sellantes biocerámicos activados por ultrasonidos en la interfase dentina-cemento radicular - Jara Castro, Marisa
To evaluate the intratubular penetration depth of ultrasound-activated bioceramic sealant cements into root dentin, specifically at the dentin-cement interface. This in vitro experimental study was conducted with samples that were randomly divided based on the type of sealer used and whether ultrasound activation was applied prior to obturation. This resulted in four experimental groups (n=40). Groups A1 and B1 utilized the Eighteeth Ultra X ultrasonic activator with a blue tip #20 featuring a 2% taper at low power for activation, while groups A2 and B2 did not employ any form of activation. The symbol (+) denotes groups with ultrasonic activation, while (-) represents groups without ultrasonic activation. In the middle third, it was observed that BioC Sealer (+) had a mean sealing value of 0.66±0.17, while MTA Fillapex (+) showed a mean value of 0.38±0.07. It was found that BioC Sealer (-) had a mean sealing value of 0.24±0.04 in the middle third, while MTA Fillapex (-) showed a mean value of 0.16±0.04. These differences were not statistically significant (p=0.569). In the apical third, the BioC Sealer (-) presented a mean sealing value of 0.44±0.17, while the MTA Fillapex (-) obtained a mean value of 0.30±0.04. However, this difference did not reach statistical significance (p=0.0745), suggesting that both materials can provide a similar seal in the apical third. The results suggest that both BioC Sealer and MTA Fillapex provide a comparable seal in the middle and apical thirds of the root canal system, however, this was not statistically significant. This indicates their potential efficacy in both endodontic sealing procedures.